Sprint Interval Training Decreases Circulating MicroRNAs Important for Muscle Development - Denham, Joshua; Gray, Adrian; Scott-Hamilton, John; Hagstrom, Amanda D. (International Journal of Sports Medicine, 2018)
Small non-coding RNAs, such as microRNAs (miRNAs), have emerged as powerful post-transcriptional regulators of gene expression that play important roles in many developmental and biological processes. In this study, we assessed the abundance of circulating microRNAs important for skeletal muscle and heart adaptations to exercise (miR-1, miR-133a, miR-133b and miR-486), following acute exercise and short-term sprint interval training (SIT). Twenty-eight individuals completed four all-out efforts on a cycle ergometer, and donated blood before and 30 min after the cessation of exercise. A subset of 10 untrained men completed 4-6 efforts of SIT, three times a week for 6 weeks, and donated resting blood samples before and after the intervention. MiRNA TaqMan qPCR was performed and whilst no changes were observed after a single session of SIT (all p>0.05), the 6-wk SIT intervention significantly reduced the whole blood content of all four miRNAs (mean fold-changes: 0.37–0.48, all p<0.01). Our data suggests that circulating miRNAs are responsive to short-term SIT and could have roles in SIT-induced health and performance adaptations. Further work is required to establish whether circulating miRNAs could serve as biomarkers for predicting exercise training responses and monitoring exercise interventions.
Keywords: epigenetics; non-coding RNA; HIIT; cardiorespiratory fitness; exercise; myomiR